Energetic Particles and Acceleration Regions Over Jupiter's Polar Cap and Main Aurora: A Broad Overview. Issue 3 (13th March 2020) - Mauk, B. H.; Clark, G.; Gladstone, G. R.; Kotsiaros, S.; Adriani, A.; Allegrini, F.; Bagenal, F.; Bolton, S. J.; Bonfond, B.; Connerney, J. E. P.; Ebert, R. W.; Haggerty, D. K.; et al.
Abstract: Previous Juno mission event studies revealed powerful electron and ion acceleration, to 100s of kiloelectron volts and higher, at low altitudes over Jupiter's main aurora and polar cap (PC; poleward of the main aurora). Here we examine 30–1200 keV JEDI‐instrument particle data from the first 16 Juno orbits to determine how common, persistent, repeatable, and ordered these processes are. For the PC regions, we find (1) upward electron angle beams, sometimes extending to megaelectron volt energies, are persistently present in essentially all portions of the polar cap but are generated by two distinct and spatially separable processes. (2) Particle evidence for megavolt downward electrostatic potentials are observable for 80% of the polar cap crossings and over substantial fractions of the PC area. For the main aurora, with the orbit favoring the duskside, we find that (1) three distinct zones are observed that are generally arranged from lower to higher latitudes but sometimes mixed. They are designated here as the diffuse aurora (DifA), Zone‐I (ZI(D)) showing primarily downward electron acceleration, and Zone‐II (ZII(B)) showing bidirectional acceleration with the upward intensities often greater than downward intensities. (2) ZI(D) and ZII(B) sometimes (but not always) contain, respectively, downward electron inverted Vs and downward proton inverted Vs, (potentials up to 400 kV) but, otherwise, have broadband distributions. (3) Surprisingly, both ZI(D) and ZII(B) can generate equally powerful auroral emissions. It is suggested but demonstrated for intense portions of only one auroral crossing, that ZI(D) and ZII(B) are associated, respectively, with upward and downward electric currents. Plain Language Summary: The science objectives of the Juno mission, with its spacecraft now orbiting Jupiter in a polar orbit, include understanding the space environments of Jupiter's polar regions and generation of Jupiter's uniquely powerful aurora. In Jupiter's polar cap regions (poleward of the main auroral oval encircling the northern and southern poles), we find here that (1) beams of electrons aligned with the upward magnetic field direction are ever‐present with energies extended to the 100s to 1, 000s of kilo electron volts and (2) downward magnetic field‐aligned electrostatic potentials reaching greater than a million volts occur over broad regions for 80% of the polar cap crossings. For the main auroral oval, we find three distinct zones: designated here as diffuse aurora (DifA), Zone‐I (ZI(D)) showing downward electron acceleration to 100s of kiloelectron volts, and Zone‐II (ZII(B)) showing bidirectional acceleration with the upward intensities often greater than downward intensities. ZI(D) sometimes shows upward electrostatic potentials reaching 100s of kilovolts and is associated with upward magnetic field‐aligned electric currents. ZII(B) sometimes shows downward electrostatic potentials reaching 100s of kilovolts and is associated with downward electric currents. Unexpectedly from Earth studies, ZI(D) and ZII(B) are just as likely to generate the most intense auroral emissions. Key Points: Jupiter's polar caps have upward electron beams essentially everywhere (100s of kiloelectron volts) and often downward megavolt electric potentials Energetic particles reveal three main auroral acceleration zones: diffuse aurora (DifA), Zone‐I (downward), and Zone‐II (bidirectional) ZI(D) and ZII(B) sometimes (but not always) contain, respectively, downward electron inverted Vs and downward proton inverted Vs